Investigation of Wall Thickness, Corrosion, and Deposits in Industrial Pipelines Using Radiographic Technique - Amoah, P.; Owusu-Poku, S.; Ajubala, G.A. (International Journal of Corrosion, 2023)
In this study, radiographic techniques were used to inspect large-diameter pipes that are used for transporting fluids in some industries in Ghana. Radiographic approaches such as the double wall technique (DWT) and tangential radiographic technique (TRT) were used to evaluate the remaining wall thickness, deposits, and corrosion in the pipes. Two steel pipes with known varying wall thicknesses ranging from 4.00 mm to 13.00 mm with a diameter of 150.00 mm were examined to authenticate the accuracy and reliability of the tangential method that was used to measure the remaining wall thickness. The tangential configuration resulted in a higher material thickness, which therefore required more time of exposure compared to the DWT method. The exposure angle of the source to the tangential part of the specimen was approximately 87° . The film generated was compared with a normal pipe piece that was not machined to serve as a control. From the radiograph obtained, an average of 6 and 7 rounded indications depicting pitting corrosion were revealed on the radiograph of the internally and externally fabricated pipe, respectively. Radiographs after the TRT revealed that the recorded wall thickness obtained from the film is about twice the value of the calculated true wall thickness.
Research Article
Keywords: Wall Thickness; double wall technique (DWT); tangential radiographic technique (TRT); Ghana